2017
DOI: 10.3949/ccjm.84a.15139
|View full text |Cite
|
Sign up to set email alerts
|

Update on viral hepatitis in pregnancy

Abstract: Pregnant women with acute viral hepatitis are at higher risk of morbidity and death than pregnant women with chronic viral hepatitis. The risk of death is highest with acute viral hepatitis E, and the rate of transmission to the baby may be highest with hepatitis B virus (HBV) infection. Managing viral hepatitis in pregnancy requires assessing the risk of transmission to the baby, determining the gestational age at the time of infection and the mother's risk of decompensation, and understanding the side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
3
0
8
Order By: Relevance
“…Bonney et al [ 14 ] found HEV to be associated with mortality in their case series from Accra Ghana. Additionally, severe HEV associated complications such as coagulation defects, fulminant hepatic failure (FHF), preterm labor, and postpartum haemorrhage are reported to be common among pregnant women in their third trimester [ 15 17 ]. Hence, HEV is a major global health problem with a disproportionately high disease burden among pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Bonney et al [ 14 ] found HEV to be associated with mortality in their case series from Accra Ghana. Additionally, severe HEV associated complications such as coagulation defects, fulminant hepatic failure (FHF), preterm labor, and postpartum haemorrhage are reported to be common among pregnant women in their third trimester [ 15 17 ]. Hence, HEV is a major global health problem with a disproportionately high disease burden among pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Сьогодні у світі вірус гепатиту В (HBV) становить глобальну проблему в сучасній охо роні здоров'я, зі змінами в епідеміології внаслі док різних факторів, включаючи вакцинацію та міграційну політику. Приблизно 2 млрд осіб у світі уражені HBV, а 20 млн ужуються щорічно, близько 240 млн -хронічні носії цього вірусу [22].…”
Section: аи ищенко нк деменинаunclassified
“…[7] . HBsAg pozitif gebeleri gözden kaçırmamak için gebelik öncesinde aşılanmış olsalar bile gebelikte HBsAg bakılması önerilmektedir [11][12][13][14] . saptanmıştır [15] .…”
Section: Abstract: Hbsag; Pregnancy; Hepatitis Bunclassified